POLITICAL AND ECONOMIC THOUGHT IN THE XIX CENTURY, THE CASE OF LATIN AMERICA - Navas-Labanda, Alegría C. (KAIRÓS, revista de ciencias económicas, jurídicas y administrativas, 2024)
The essay analyzes the adjustment of the ideas of classical liberalism in Latin America in the nineteenth century. Within a historiographical, hermeneutical, and analytical methodology of some cases that exemplify political and economic ideas, a general conclusion has been reached: the ideas of classical liberalism became a superficial mask that concealed democratic systems and flimsy capitalists. On the political side, specific benefits to the Catholic Church were hidden under the mask; however, in specific periods, some examples, even with liberal denominations, show that the persecution of clerics was also hidden or underestimated. On the economic side, the benefits of free markets will not be seen until the second half of the 19th century, when the Industrial Revolution caused Europe and the United States to increase their demand for raw materials